2019
DOI: 10.1186/s12882-019-1583-8
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerotic vascular disease is more prevalent among black ESKD patients on long-term CAPD in South Africa

Abstract: BackgroundOccurrence of cardiovascular disease (CVD) in the setting of chronic kidney disease (CKD) can be described as a “cruel alliance”, with CVD responsible for about half of all deaths among CKD patients. Chronic kidney disease patients are more likely to die from CVD than progress to end stage kidney disease (ESKD). Dyslipidaemia, a known traditional risk factor for CVD, is highly prevalent among CKD patients and with an even higher frequency among ESKD patients on dialytic therapies. Prolonged exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Among black CKD patients receiving care in a tertiary health facility in South Africa, we reported a higher prevalence of carotid atherosclerotic vascular disease (AsVD) in stage 3 CKD and ESKD patients compared to controls. AsVD was more prevalent among peritoneal dialysis (PD) patients compared to haemodialysis (HD) and CKD stage 3 patients [5]. In a previous study, we also reported an increased prevalence of left ventricular hypertrophy (LVH) among kidney transplant recipients compared to controls [6].…”
Section: Overview Of Cvd In Ckdmentioning
confidence: 81%
See 1 more Smart Citation
“…Among black CKD patients receiving care in a tertiary health facility in South Africa, we reported a higher prevalence of carotid atherosclerotic vascular disease (AsVD) in stage 3 CKD and ESKD patients compared to controls. AsVD was more prevalent among peritoneal dialysis (PD) patients compared to haemodialysis (HD) and CKD stage 3 patients [5]. In a previous study, we also reported an increased prevalence of left ventricular hypertrophy (LVH) among kidney transplant recipients compared to controls [6].…”
Section: Overview Of Cvd In Ckdmentioning
confidence: 81%
“…In a previous study, we evaluated the prevalence of AsVD and its predictors among Black patients with stage 3 CKD or ESKD on continuous ambulatory peritoneal dialysis (CAPD) or HD. AsVD was most prevalent among CAPD patients, occurring in 70%, compared to 47.5% among HD patients and 17.1% among controls [5]. Similarly, Go et al [10] reported an association between lower GFR and CVD.…”
Section: Epidemiology Of Cvd In Ckdmentioning
confidence: 91%
“…As a result, most affected individuals are unaware of their disease status, and are often only detected at an advanced stage of the disease [ 3 ]. Furthermore, CKD is an independent risk factor for cardiovascular disease (CVD), and individuals with CKD are more likely to die of CVDs than progress to end-stage kidney disease (ESKD) [ 4 ]. Early diagnosis of CKD and effective screening of high-risk individuals is critical to mitigate disease progression and substantially reduce related poor health outcomes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%